"I want to do it all day!"—Students' experiences of classroom movement integration. (2019) - McMullen, Jaimie M.; MacPhail, Ann; Dillon, Michelle
Highlights: Movement integration in classrooms is an effective way to increase physical activity levels. Primary school students believe movement lessons are fun and that they help them learn. Primary school students connect movement in the classroom to their fitness development. Students positively perceive movement in the classroom and want more movement in school. Abstract: Whole-of-school physical activity programming is being advocated internationally, with movement integration in the classroom considered an effective method to increase physical activity throughout the school day. Students (N = 135) from two primary schools in the West of Ireland participated in this study. Data were collected using draw-and-write (N = 135) and focus group interviews (N = 24). Three themes were evident across data types and revealed that students thought the Moving to Learn Ireland active lessons were fun, that they learned academic content better, and the lessons contributed to their fitness development. In conclusion, children who participated in this study positively perceived movement integration lessons in their classrooms. The results of this study can inform future movement integration interventions.